Prognostic value of molecular cytology by one-step nucleic acid amplification (OSNA) assay of peritoneal washings in advanced gastric cancer patients - Katarzyna Gęca; Magdalena Skórzewska; Karol Rawicz-Pruszyński; Radosław Mlak; Katarzyna Sędłak; Zuzanna Pelc; Teresa Małecka-Massalska; Wojciech P. Polkowski (Scientific Reports, 2022)
Abstract Peritoneal dissemination is a common form of gastric cancer (GC) recurrence, despite surgery with curative intent. This study aimed to evaluate the prognostic value of intraperitoneal lavage One-Step Nucleic Acid Amplification (OSNA) assay in advanced GC patients. OSNA assay targeting CK-19 mRNA was applied to detect free cancer cells (FCC) in intraperitoneal lavage samples obtained during gastrectomy. A total of 82 GC patients were enrolled to investigate the correlation between OSNA assay and patient’s prognosis. Of the 82 patients, OSNA assay was positive in 25 (30.5%) patients. The median OS in OSNA positive patients was significantly lower than in OSNA negative patients (19 vs 45 months). Positive OSNA assay result was a significant unfavourable prognostic factor in both, univariable (HR 3.45, 95% CI 0.95–12.48; p = 0.0030) and multivariable analysis (HR 3.10, 95% CI 1.22–8.54; p = 0.0298). Positive OSNA assay in intraperitoneal lavage is a valuable indicator of poor survival in advanced GC patients after multimodal treatment. After further confirmation on larger sample size, OSNA assay of peritoneal washings could be considered an adjunct tool to conventional cytology, the current gold standard, to provide precise intraoperative staging and additional prognostic information.